1970
DOI: 10.1159/000466036
|View full text |Cite
|
Sign up to set email alerts
|

The Sd^a Blood Group Antigen in Tissues and Body Fluids

Abstract: In man the Sd^a antigen is present in most secretions with the greatest concentration in urine. There is little difference in the amount of Sd^a substance in the urine of newborn infants, pregnant women and normal adults but there is a much greater amount in the saliva of newborn infants than in adults. Approximately half the people whose red cells group as Sd(a-) secrete Sd^a substance in the urine. Anti-Sd^a antibody is present in 50% of Sd(a-) non-secretors of Sda substance, though most of these antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 7 publications
2
58
0
Order By: Relevance
“…The peculiarity of this blood group is that the human naturally occurring antibodies agglutinate only a pro portion of red cells, even from donors with high expression of Sda antigen. Morton et al [6] found a positive activity also in body tis sues and fluids. Because of the high presence of Sda activity in urine they proposed a reac tion for the determination of Sda antigenic constitution based on the inhibition of Sda agglutination by urine.…”
Section: Introductionmentioning
confidence: 94%
“…The peculiarity of this blood group is that the human naturally occurring antibodies agglutinate only a pro portion of red cells, even from donors with high expression of Sda antigen. Morton et al [6] found a positive activity also in body tis sues and fluids. Because of the high presence of Sda activity in urine they proposed a reac tion for the determination of Sda antigenic constitution based on the inhibition of Sda agglutination by urine.…”
Section: Introductionmentioning
confidence: 94%
“…The presence or ab sence of the antigen on red cells, but not in urine, is related to pregnancy. Macvie et al [1] and Morton et al [3] found an increased percentage of pregnant women with Sd(a-) red cells. Many of these patients had Sd(a+) red cells following delivery.…”
Section: Introductionmentioning
confidence: 95%
“…The Sd blood group system was first de scribed in 1967 by Macvie et al [1] and Ren ton et al [2], Approximately 96% of the pop ulation have the Sda antigen present on their red blood cells or in their urine [3]. Rare individuals have a very strong Sda antigen, denoted as Sd(a++) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood group substances with Sd ~ activity occur in most human secretions, with the highest concentration in urine and meconium [1][2][3][4]. It was found that the GalNAc~I ~ residues make an important contribution to the Sd a determinant structure in Tamm-Horsfall glycoprotein (THGP) [5].…”
Section: Introductionmentioning
confidence: 99%